Karakteristik Morfologi Dasar Laut dan Hubungannya dengan Ketebalan Sedimen dan Kecepatan Arus di Selat Flores, Selat Lamakera, Selat Boling, dan Selat Alor - Muhammad Hasanudin (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Characteristics of Sea Bottom Morphology and Their Relationships with Sediment Thickness and Current Speed in the Straits of Flores, Lamakera, Boling, and Alor. The morphology of the seabed of a strait may affect sedimentary deposits and current speeds in the strait. The Straits of Flores, Lamakera, Boling, and Alor connect the Flores Sea and Savu Sea in East Nusa Tenggara Province. This study aimed to determine the characteristics of seabed morphology and its relation to sediment thickness and current speed in the straits. Single Beam Echosounder and SubBottom Profiler were used to measure depth of waters and subsurface. The results showed that the seabed of the Flores Strait was basin-shaped at a depth of about 250 m, while the seabed at the connections between the Straits of Boling, Lamakera, and Alor was a ridge leading to the Flores Sea and Savu Sea with depths up to 3,000 m. The thickness of the sedimentary sediments in the Flores Strait reached 50 m, while in the Straits of Boling, Lamakera, and Alor sedimentary deposits were not visible. In the Flores Strait which was characterized by narrow strait, the current speed ranged from 0.3 to 3.8 m/s. The descriptions of subsurface conditions in these straits can be used for navigation of ships that will cross the straits, especially vessels of more than 2,000 tons. The narrow strait morphology causes the mass of water in this region to have a high current speed. Therefore, the sedimentation occurs only in the Flores Strait due to its basin-shaped seabed.